SHORTCUT TO LATEX - Rathiah Hashim (2012)
This book is an introduction to LaTeX for those who have not used LaTeX before. It is a wonderful software to typeset your document and especially helpful for post graduate students to write and structure their theses or dissertations. With LaTeX, you can effectively integrate your text with tables, figures, math symbols and references. The approach in this book is dedicated to Window users. The beauty about LaTeX is that you don’t really need to know everything. Most people only learn the basics and upgrade their skills continuously using internet resources.Some Highlights:  •    Installation process  •    The right package to install for different purposes  •    A lot of tips on how to get help from the internet  •    The first few important steps in getting started  •    The essential basics in preparing your technical and scientific document  •    A lot of exercises to follow with illustration of screen shots  •    Step by step examples on different topics